Supercritical fluid chromatography with post‐column addition of supporting electrolyte solution for electrochemical determination of tocopherol and tocotrienol isomers. Issue 10 (17th March 2022) - Yamamoto, Kazuhiro; Nishimura, Takuma; Machida, Koichi; Kotani, Akira; Hakamata, Hideki
Abstract : A supercritical fluid chromatography with electrochemical detection system was developed for the simultaneous determination of tocopherol and tocotrienol isomers. The supercritical fluid chromatography with electrochemical detection system was connected with an additional pump to create a flow path to add a supporting electrolyte solution. The supporting electrolyte solution was mixed with a mobile phase in a post‐column fashion, enabling the independent control of the separation and detection. After optimization of the measurement conditions, vitamin E isomers and an internal standard substance (2, 2, 5, 7, 8‐pentamethyl‐6‐hydroxychroman) were separated within 30 min using a mixture of supercritical carbon dioxide and methanol (99:1, v/v) as a mobile phase and a cyanopropyl column (4.6 mm inner diameter × 250 mm length, 5 μm). For the electrochemical detection, methanol containing 1.0 mol/L ammonium acetate was used as a supporting electrolyte solution, and the applied potential was set at +0.8 V. This analytical method showed good linearity (5–100 μg/mL) and repeatability (less than 2.5% relative standard deviation, n  = 6) and was applicable to the determination of tocopherol and tocotrienol isomers in nutrition supplements.